The Invention of Judeo-Arabic: Nation, Partition and the Linguistic Imaginary. Issue 2 (17th February 2017) - Shohat, Ella
Abstract : This essay examines the issue of linguistic belonging as invented within national and colonial itineraries. More specifically, it explores the genealogy of the notion of 'Judeo-Arabic language' and its axiomatic definition as a cohesive unit separate from Arabic. Underscoring instead the terms deployed by Arabic-speaking Jews themselves, the essay asks whether the concept of 'Judeo-Arabic, ' proposed by contemporary linguists, corresponds to the naming within the language itself or rather to a paradigm influenced by post-Haskala (Enlightenment) Judaic studies and Jewish nationalism. While recognizing the specificities of the Arabic(s) deployed by Jews, the essay interrogates the view of 'Judeo-Arabic' as classifiable under the historically novel rubric of isolatable 'Jewish languages' severed from their neighboring dialect/languages, in this case Arabic. It also casts doubt on an 'endangered language' discourse premised on the Arabic/Judeo-Arabic split, by asking whether the idea of a salvage project for a 'dying language' does not reproduce the same conceptual binaries that produced the disappearance of 'the language' in the first place. Despite demographic dislocation from Arab spaces in the wake of Palestine's partition, the essay suggests, the Arabic(s) spoken by Jews have always been and have remained intimately linked, even now across the Israeli/Arab divide, forming part of a living assemblage of Arabic variations. Examining Arabic vernaculars as performed along a discursive spectrum from erudite to popular culture, the essay highlights Arabic/Hebrew syncretism, tracing the presence of Arabic, for example, in music and literature. Within a transnational approach, the essay stresses the phantasmatic dimension that led to 'Judeo-Arabic, ' in the wake of its displacement from Arabic-speaking cultural geographies, being simultaneously rejected and desired.